International Monetary Transmission with Bank Heterogeneity and Default Risk - Tsvetomira Tsenova (FIW - Research Centre International Economics, 2013)
This paper compares the effectiveness, efficiency and robustness of standard and non-standard monetary policy tools, such as the banks' refinancing interest rate, penalty interest rate on deposit facility holdings and minimum reserve requirements on attracted deposits. The assessment is performed on the basis of a numerically evaluated open economy general equilibrium model for macro-prudential analysis where optimal decisions by internationally linked banks are key determinants of international financial flows and wider economic outcomes. Banks differ in terms of balance sheet endowments and risk preferences, and take decisions rationally and competitively. Default risk, borrowing and lending are endogenous results of individual decisions of private agents (banks and households), as well as systemic outcomes of market interaction.
Keywords: C68; D58; E44; E51; E52; E58; G21; 330; Banking; Monetary Policy; Non-standard Instruments; Macro-Prudential Policies; Financial Stability; Contingency Planning